EFFECT OF ENERGETIC ION BOMBARDMENT DURING THE GROWTH OF HYDROGENATED AMORPHOUS CARBON THIN FILMS - Aijaz, Asim; Uddin, Zaheer (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Hydrogenated amorphous carbon (a-C:H) thin film growth using plasma-assisted deposition is studied using Monte Carlo based simulation. The effect of energetic bombardment of the ionized depositing species as well as ionized buffer gas species on the film growth and the resulting film properties is investigated. The ion energies that assist the a-C:H film growth from low density structures to high density structures such as diamond-like carbon (DLC) are used and the effect of energy and composition of the depositing species on the C-C and C-H bonding and the film structure are analyzed. It is found that the ion bombardment favors the formation of a-C:H films with low H contents, high density and superior mechanical strength of the resulting thin films and is therefore an effective way to tailor-made a-C:H thin film growth for specific applications.